Persepsi Dan Preferensi Pengunjung terhadap Aplikasi Desain Youth Park Denpasar - Rafikhudin, Agus Rifkhi; Yusiana, Lury Sevita; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023DO - 10.24843/JAL.2023.v09.i02.p02, 2023)
Visitors' Perceptions and Preferences on the Denpasar Youth Park Design Application . Youth Park Denpasar is one of the parks located in Denpasar which was created to flow the ideas and creativity of young people in Denpasar. The construction of Youth Park Denpasar which has facilities that support several activities among young people, it is necessary to have a design application or application of a good function according to the tastes and trends of today's youth, where an attractive appearance can affect the level of visitors to Youth Park Denpasar. In order to improve the appearance of Youth Park Denpasar, there is a need for research on the perceptions and preferences of park visitors. This study aims to identify the perceptions and preferences of visitors to the youth park and make recommendations as a solution. The study used a survey method with data collection techniques in the form of observation, interviews, literature study, and questionnaires, that collected 30 copies for 30 respondents. The visitor's perception of the Denpasar Youth Park design application showed that most of them said it was good. Visitors' preferences for the Denpasar Youth Park design application show that the form of parking, lighting and still need to be improved. Visitors' perceptions and preferences of the Denpasar Youth Park design application are used as information in the future development of Youth Park Denpasar or as a reference for making other parks, so that Youth Park Denpasar can be used optimally and comfortably according to visitors.